Evolutionary dynamics of transposable elements in the short-tailed opossum Monodelphis domestica - Gentles, Andrew J.; Wakefield, Matthew J.; Kohany, Oleksiy; Gu, Wanjun; Batzer, Mark A.; Pollock, David D.; Jurka, Jerzy

(untitled) (Genome Research, 2007)
The genome of the gray short-tailed opossum Monodelphis domestica is notable for its large size (∼3.6 Gb). We characterized nearly 500 families of interspersed repeats from the Monodelphis. They cover ∼52% of the genome, higher than in any other amniotic lineage studied to date, and may account for the unusually large genome size. In comparison to other mammals, Monodelphis is significantly rich in non-LTR retrotransposons from the LINE-1, CR1, and RTE families, with >29% of the genome sequence comprised of copies of these elements. Monodelphis has at least four families of RTE, and we report support for horizontal transfer of this non-LTR retrotransposon. In addition to short interspersed elements (SINEs) mobilized by L1, we found several families of SINEs that appear to use RTE elements for mobilization. In contrast to L1-mobilized SINEs, the RTE-mobilized SINEs in Monodelphis appear to shift from G+C-rich to G+C-low regions with time. Endogenous retroviruses have colonized ∼10% of the opossum genome. We found that their density is enhanced in centromeric and/or telomeric regions of most Monodelphis chromosomes. We identified 83 new families of ancient repeats that are highly conserved across amniotic lineages, including 14 LINE-derived repeats; and a novel SINE element, MER131, that may have been exapted as a highly conserved functional noncoding RNA, and whose emergence dates back to ∼300 million years ago. Many of these conserved repeats are also present in human, and are highly over-represented in predicted cis-regulatory modules. Seventy-six of the 83 families are present in chicken in addition to mammals.